Pengkaryaan drama radio kepada anggota Bengkel Sastra FBS UNM sebagai media alternatif pelestarian cerita rakyat - Khaeruddin Khaeruddin; Prusdianto Prusdianto (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Folklore is a story that originates from thecommunity and develops in society in a descending way and itis delivered orally. The younger generation at this time hasbegun to be less interested in folklore because it is deemedirrelevant to the times of the modern era of globalization. Theydo not realize that there are many moral stories in folklore.Based on that problem, the community action program wasmade. The program title was “Creating Radio Drama by themembers of Literary Studio of FBS UNM". It aimed to makefolklore packed in audio media as an alternative medium.Thus, people who are involved in the activity do not onlyknow the contents of the story but also feel the events thathappened in that folklore. In the end, they will find out themoral stories of folklore that is made so that the story remainssustainable as a cultural wealth that is owned. The activity wascarried out at the Literary Studio of FBS UNM which tookplace at Daeng Tata Raya Street, UNM Parang TambungCampus. This activity resulted; (1) the radio drama becomes anew media to be done in the Literary Studio of FBS UNM, (2)through this activity, the members of the Literary Studio ofFBS UNM are familiar with radio drama and know the workprocess of its creation which is a creative work process thatprioritizes audio as an art expression medium, (3) the radiodrama is produced based on folklore and eventually becomesan alternative media for preservation.